Comparing Diuresis Patterns in Hospitalized Patients With Heart Failure With Reduced Versus Preserved Ejection Fraction: A Retrospective Analysis. (March 2021) - Broscious, Rachael; Kukin, Alina; Noel, Zachary R.; Devabhakthuni, Sandeep; Seung, Hyunuk; Ramani, Gautam V.; Reed, Brent N.
Background: Congestion predominates in exacerbations of heart failure with reduced ejection fraction (HFrEF) or preserved ejection fraction (HFpEF), but evidence suggests that excess volume may be distributed differently in these 2 subgroups. Methods and Results: In this retrospective study, diuretic efficiency (DE, or net urine output per 40-mg of intravenous furosemide equivalent) during the first 72 hours was compared between patients hospitalized with HFrEF (n = 121) versus HFpEF (n = 120). Multivariate analysis was used to compare the 2 groups based on expected baseline differences (e.g., demographics, heart failure etiology, concomitant therapy). During the first 72 hours, mean daily diuretic doses were higher in patients with HFpEF versus HFrEF (172.0 vs. 159.9 mg, respectively, P = 0.026) but urine output was not significantly different (2603.3 mL vs. 2667.5 mL, respectively, adjusted P = 0.100). Similarly, mean cumulative DE did not differ (−673.5 vs. −637.8 mL/40-mg in the HFrEF and HFpEF groups, respectively, adjusted P = 0.884). An exploratory analysis of propensity-matched cohorts yielded similar findings. Correlations between the components of DE varied considerably and only became weak to moderately correlated toward the end of the observation period. Conclusions: Although cumulative DE did not differ between patients with HFrEF and HFpEF, variable correlations in the components of DE suggest there may be differences in diuretic response that warrant future analysis.